The RNA Methylation Modification 5-Methylcytosine Impacts Immunity Characteristics, Prognosis and Progression of Oral Squamous Cell Carcinoma by Bioinformatics Analysis - Gao, Li; Chen, Ru; Sugimoto, Masahiro; Mizuta, Masanobu; Zhou, Lei; Kishimoto, Yo; Huang, Xinsheng; Omori, Koichi (Frontiers in Bioengineering and Biotechnology, 2021)
Disorders pertaining to 5-methylcytosine (m5C) modifications are involved in the pathological process of many diseases. However, the effect of m5C on the occurrence and progression of oral squamous cell carcinoma (OSCC) remains unclear. Based on 16 m5C methylation regulators, two m5C modification patterns were identified with distinct tumor immune microenvironment (TIME) characteristics and prognosis in OSCC. We then performed weighted gene co-expression network analysis (WGCNA) to identify m5C modification cluster-related modules. Genes in the selected module were chosen to construct the m5Cscore scoring system for evaluation of the m5C modification pattern in individual OSCC patients. Patients with a high m5Cscore had higher immune, stromal, and ESTIMATE scores; lower tumor purity score; lower enrichment scores in most immune cell types; and higher tumor mutational burden. The overall survival rate and progression-free survival rate were markedly worse and the tumor recurrence rate was higher in OSCC patients with a high m5Cscore. Furthermore, patients with oral leukoplakia who also had a high m5Cscore had a higher risk of deterioration to OSCC. This study demonstrated that m5C modification patterns were associated with the TIME in OSCC. m5C modification patterns and m5Cscore have potential prediction ability in the progress and prognosis of OSCC.